(untitled) (Kanun: Jurnal Undang-undang Malaysia, 2019)
Uncontrollable information-sharing may cause some legal issues. The recent trend is that parents are eager to share information regarding their children freely and without restrictions via the Internet. This is known as ’sharenting’. The sharing of such information must be viewed in terms of the security of personal information, confidentiality and privacy. The aim of this article is to take a holistic look at the issue of sharenting by examining the necessity of legal controls. This research is a qualitative socio-legal research that studies the implication of sharenting in the current situation, and the adequacy of existing legal protection. The research reveals that there is a need for this issue to be looked at more seriously and that improvements to existing laws are necessary to provide more comprehensive protection to children. Keywords: sharenting, information-sharing, parental rights, childrens’ rights, legal protection